Vibrational relaxation beyond the linear damping limit in two-dimensional optical spectra of molecular aggregates - Perlík, Václav; Šanda, František (The Journal of chemical physics, 2017)
We present a computational model for the spectra of molecular aggregates with signatures of vibronic progression. Vibronic dynamics is implemented by coupling the dynamics of Frenkel excitons with underdamped vibrations. Vibrational dynamics includes linear damping resulting in the exponential decay and quadratic damping inducing subexponential or power law relaxation and increasing vibrational decoherence as demonstrated on lineshapes of the absorption spectrum. Simulations of the third-order coherent response account for bath reorganization during excitonic transport, which allows us to study the line-shape evolution of cross peaks of 2D spectra.